Structure–Relaxivity Relationships of Magnetic Nanoparticles for Magnetic Resonance Imaging - Zhou, Zijian; Yang, Lijiao; Gao, Jinhao; Chen, Xiaoyuan (Advanced materials (Weinheim), 2019)
Magnetic nanoparticles (MNPs) have been extensively explored as magnetic resonance imaging (MRI) contrast agents. With the increasing complexity in the structure of modern MNPs, the classical Solomon–Bloembergen–Morgan and the outer‐sphere quantum mechanical theories established on simplistic models have encountered limitations for defining the emergent phenomena of relaxation enhancement in MRI. Recent progress in probing MRI relaxivity of MNPs based on structural features at the molecular and atomic scales is reviewed, namely, the structure–relaxivity relationships, including size, shape, crystal structure, surface modification, and assembled structure. A special emphasis is placed on bridging the gaps between classical simplistic models and modern MNPs with elegant structural complexity. In the pursuit of novel MRI contrast agents, it is hoped that this review will spur the critical thinking for design and engineering of novel MNPs for MRI applications across a broad spectrum of research fields. Structure–relaxivity relationships between different structural features of magnetic nanoparticles (MNPs) and the resulting T1 and T2 relaxivities in magnetic resonance imaging (MRI) are reviewed. The factors of size, shape, crystal structure, surface functionality, and assembly structure of magnetic nanoparticles are summarized to decipher how physical properties of MNPs influence proton relaxation in MRI.